Methodology of Teaching the Topic of Cylinder, Its Surface and Volume Using Problem-Based Learning Technology - Ismoilov Elmurod Olloberdi o‘g‘li (Academia One Publishing, 2023)
The article describes how to teach the theme "Cylinder, its surface and volume" using problem educational technology. In addition, in the article provides a number of suggestions and methodical recommendations for teachers on how to use pedagogical technology.
Keywords: cylinder; surface; volume; stereometry